Genetic counseling development and milestone in Oman - Khalsa Al-Kharusi; Chantel Van Wyk; Mariya Al Hinai; Amel Al-Fori; Zandre Bruwer (Genetics in Medicine Open)
Genetic counseling as an emerging profession has seen an expansion around the world. In the Sultanate of Oman, the profession has developed with the establishment of clinical and biochemical genetic services in 2010 and genetic counseling services in 2011. Currently, 3 main genetic counseling teams serve the country through qualified genetic counselors who completed internationally recognized MSc program. The genetic counselors are working in governmental clinical genetic units and play vital roles in enhancing the quality of genetic services dealing with pediatric and adult-onset disorders. The impact of the service is reflected in the escalated demand for preventative measures, such as alternative reproductive options, premarital genetic counseling and testing, and predictive counseling and testing. Despite the limited resources and absence of a licensing body, the genetic counseling profession in Oman is progressing. This special report describes the development of genetic counseling in Oman and the milestones reached. It details the areas of service, scope of practice, and the unique social and cultural nuances inherent to genetic counseling in Oman.